Histoarchitectural Study of Corpus Luteumin Pregnant and Non-Pregnant State - Masooma Syed; Waqar Akram; M.Tariq Zaidi (Academia Anatomica International, 2019)
Introduction: The fate and the life span of the corpus luteum depends upon whether fertilization occurs or not. In the present study we have compared the histology of corpus luteum of early pregnancy with a non-pregnant state.Subjects and Methods: Tissue was collected during a pan hysterectomy for uncontrolled bleeding in a ruptured ectopic pregnancy and prepared for histology. The slides were compared with slides from ovary of a non-pregnant female present in the department of anatomy at JNMC, Aligarh.Results: The pregnant state had the fibroblast layer which was wider and granulosa luteal layer was more cellular in comparison to the non-pregnant state.Conclusion: In depth knowledge of the changes taking place in corpus luteum will increase our understanding of luteal dysfunction. More studies with advanced techniques are needed to further increase our knowledge.